Autumn - Moody, David, 1970- (New York Thomas Dunne Books, 2010)
A hybrid of War of the worlds and Night of the living dead, chronicles the struggle of a small group of survivors forced to contend with a world torn apart by a deadly disease.
111018
Keywords: Regression (Civilization) -- Fiction; Survival -- Fiction; Zombies -- Fiction; Horror fiction, English; Dystopias; Fantasy fiction; Fiction